Intersecting epidemics of HIV, HCV, and syphilis among soon-to-be released prisoners in Kyrgyzstan: Implications for prevention and treatment - Azbel, L.; Polonsky, M.; Wegman, M.; Shumskaya, N.; Kurmanalieva, A.; Asanov, A.; Wickersham, J.A.; Dvoriak, S.; Altice, F.L. (Elsevier, 2016)
Background Central Asia is afflicted with increasing HIV incidence, low antiretroviral therapy (ART) coverage and increasing AIDS mortality, driven primarily by people who inject drugs (PWID). Reliable data about HIV, other infectious diseases, and substance use disorders in prisoners in this region is lacking and could provide important insights into how to improve HIV prevention and treatment efforts in the region. Methods A randomly sampled, nationwide biobehavioural health survey was conducted in 8 prisons in Kyrgyzstan among all soon-to-be-released prisoners; women were oversampled. Consented participants underwent computer-assisted, standardized behavioural health assessment surveys and testing for HIV, HCV, HBV, and syphilis. Prevalence and means were computed, and generalized linear modelling was conducted, with all analyses using weights to account for disproportionate sampling by strata. Results Among 381 prisoners who underwent consent procedures, 368 (96.6%) were enrolled in the study. Women were significantly older than men (40.6 vs. 36.5; p = 0.004). Weighted prevalence (%), with confidence interval (CI), for each infection was high: HCV (49.7%; CI: 44.8–54.6%), syphilis (19.2%; CI: 15.1–23.5%), HIV (10.3%; CI: 6.9–13.8%), and HBV (6.2%; CI: 3.6–8.9%). Among the 31 people with HIV, 46.5% were aware of being HIV-infected. Men, compared to women, were significantly more likely to have injected drugs (38.3% vs.16.0%; p = 0.001). Pre-incarceration and within-prison drug injection, primarily of opioids, was 35.4% and 30.8%, respectively. Independent correlates of HIV infection included lifetime drug injection (adjusted odds ratio [AOR] = 38.75; p = 0.001), mean number of years injecting (AOR = 0.93; p = 0.018), mean number of days experiencing drug problems (AOR = 1.09; p = 0.025), increasing duration of imprisonment (AOR = 1.08; p = 0.02 for each year) and having syphilis (AOR = 3.51; p = 0.003), while being female (AOR = 3.06; p = 0.004) and being a recidivist offender (AOR = 2.67; p = 0.008) were independently correlated with syphilis infection. Conclusion Drug injection, syphilis co-infection, and exposure to increased risk during incarceration are likely to be important contributors to HIV transmission among prisoners in Kyrgyzstan. Compared to the community, HIV is concentrated 34-fold higher in prisoners. A high proportion of undiagnosed syphilis and HIV infections presents a significant gap in the HIV care continuum. Findings highlight the critical importance of evidence-based responses within prison, including enhanced testing for HIV and sexually transmitted infections, to stem the evolving HIV epidemic in the region.